GAMBARAN DUPLEX ULTRASONOGRAFI EKSTREMITAS BAWAH PADA PASIEN PERIPHERAL ARTERY DISEASE DI RSUD PASAR REBO - Rahayu, Adelia Ika; Chandranegara, Agung Fabian; Jamaluddin, Ahmad (ARKAVI [Arsip Kardiovaskular Indonesia], 2025)
Backgroud: Duplex ultrasound examination performed in peripheral artery disease (PAD). PAD is a condition of narrowing blood vessels caused by plaque buildup in arteries and resulting in decreased perfusion in the extremities. Method: Case Report, in PAD patients with lower extremity ultrasound duplex examination at Pasar Rebo Hospital Results: Lower extremity DUS examination technique was performed on patient, the first patient found plaque and sec/echogenic material in Poplitea, color Doppler partially filled color and monophasic Doppler spectrum. The second patient had sec in the femoral, B-Mode plaques were found in popliteal color Doppler partially filled color and monophasic Doppler spectrum. Conclusion: The duplex ultrasound examination procedure has been successfully performed on both patients with CAD and CHF. Procedures for preparing equipment, patients and examinations are carried out in accordance with operational standards at Pasar Rebo Hospital. B-Mode, color Doppler and Doppler spectrum according to PAD.